Menilik Kembali Titik Temu Agama-Agama Perspektif Ibnu Arabi - Arrasyid Arrasyid; Susilawati Susilawati (Al-Adyan: Journal of Religious Studies, 2022)
The ongoing conflict in various parts of Indonesia shows the lack of religious views on the harmonization or relation of religions. So it is necessary to present the concept of religious unity of Ibn Arabi so that the view of the common word of religions can exist in the lives of religious adherents. This study was analyzed by qualitative research using exploratory methods and content analysis. The findings obtained are that with religious unity, Ibn Arabi wants to discuss the common word of religions, namely common word towards facing the One and Same God, although with various religious names and symbols. The differences that exist in each religion are only outward matters, but inwardly they are serving the One and the Same God. Thus, the existing differences are not a problem, on the contrary the existing similarities, should be put forward so that conflicts between religious communities can be resolved. Masih terjadinya konflik di berbagai wilayah Indonesia menunjukkan kurangnya pandangan penganut agama tentang harmonisasi atau relasi agama-agama. Sehingga dirasa perlu untuk menghadirkan konsep kesatuan agama Ibnu Arabi agar pandangan tentang titik temu agama-agama bisa eksis dalam kehidupan penganut agama. Penelitian ini dianalisis dengan penelitian kualitatif menggunakan metode eksploratif dan analisis isi. Adapun temuan yang diperoleh bahwa dengan kesatuan agama Ibnu Arabi ingin mewacanakan titik temu agama-agama, yaitu bertitik temu pada menghadap kepada Tuhan Yang Satu dan Sama, walau dengan nama dan simbol agama yang beragam. Perbedaan yang ada pada setiap agama hanyalah persoalan lahiriyah, namun secara batiniyah sedang menghamba kepada Tuhan Satu dan Sama. Maka, perbedaan yang ada bukanlah persoalan, sebaliknya persamaan yang ada, hendaknya dikedepankan agar konflik antara umat beragama dapat terselesaikan.